A Design Of Automatic Safety Equipment For Lpg Gas Stoves Based On Atmega 8 Microcontroller - Hermansyah Alam (Jurnal Info Sains : Informatika dan Sains, 2023)
The LPG gas stove explosion was the result of an LPG gas leak and an increase in the temperature of the gas stove frame. In this research, an early warning system is needed regarding the dangers of using LPG gas stoves. this paper discuseed about a gas stove safety device designed based on the Atmega 8 microcontroller through gas flow. The use of several sensors such as a gas sensor to detect LPG gas content with a concentration range of 200 – 10,000 mg/L, and a Selenoid Valve which functions as a gas flow breaker to the stove. Also a buzzer as a warning tool when a leak occurs. Apart from that, a timer with a maximum working process of 15 minutes will automatically turn off the stove when the desired time is reached. The entire system can work automatically or manually depending on your needs. After testing it turned out to be true when a gas leak occurred, the system can turn off the stove automatically. Likewise, it shows that if the gas leak detection distance is farther, the system response time will slow down.